1989
DOI: 10.1111/j.1365-2141.1989.tb04296.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of interleuk:in‐2 secretion by factor VIII concentrates: a possible cause of immunosuppression in haemophiliacs

Abstract: Summary The inhibitory effect of factor VIII concentrate products on IL‐2 secretion by human T‐cells was investigated. The six products used widely in the lJ.K. showed very different activities varying from almost total inhibition to no significant effect. There appeared to be no obvious relationship between inhibitory activity and protein composition but factor VIII itself was not responsible for the effect as affinity purified products were entirely non‐inhibitory. The two wetheated products were most inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Moreover, a role of the immunomodulating impurities in the relative success of the study product cannot be definitely excluded. In effect, the plasmaderived clotting factor concentratesÕ content of soluble human leukocyte antigen system (HLA) class I antigens, soluble Fas-ligand and transforming growth factor b 1 have a measurable in vitro immunosuppressive activity as showed by Ghio et al [24], confirming previous findings [25,[30][31][32][33][34][35][36][37]. Nevertheless, Ghio et al [24], who assayed the concentrations of these molecules in clotting factor concentrates, showed that the product used in this study have no immunoglobulin, fibrinogen and fibronectin, and a very low concentration of these other immunosuppressive molecules, comparable with monoclonally purified plasma-derived FVIII products.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, a role of the immunomodulating impurities in the relative success of the study product cannot be definitely excluded. In effect, the plasmaderived clotting factor concentratesÕ content of soluble human leukocyte antigen system (HLA) class I antigens, soluble Fas-ligand and transforming growth factor b 1 have a measurable in vitro immunosuppressive activity as showed by Ghio et al [24], confirming previous findings [25,[30][31][32][33][34][35][36][37]. Nevertheless, Ghio et al [24], who assayed the concentrations of these molecules in clotting factor concentrates, showed that the product used in this study have no immunoglobulin, fibrinogen and fibronectin, and a very low concentration of these other immunosuppressive molecules, comparable with monoclonally purified plasma-derived FVIII products.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, patients who had failed ITI with a monoclonally purified concentrate (either recombinant or plasma derived) very poor in VWF, achieved and maintained immune tolerance when VWF/FVIII complex concentrates were used [23]. Other Clinicians have suggested that the impurities of plasmaderived concentrates and not their content in VWF might play a role by means of their immunomodulating activity [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Whether this advantage is due to VWF or to other immunomodulatory substances that are present in intermediate purity preparations is not clear. Previously, intermediate purity, but not high purity, FVIII products were shown to express immunomodulatory activity in vitro (Thorpe et al , 1989; Wadhwa et al , 1992). Part of this immunomodulatory activity seems to be due to the presence of immunomodulatory cytokines, such as transforming growth factor beta (Wadhwa et al , 1994; Hodge et al , 1999; Berntorp, 2001; Hodge & Han, 2001).…”
Section: Immune Tolerance Induction Therapy In Patients With Fviii Inmentioning
confidence: 99%
“…FVIII products have been shown to inhibit lymphocyte proliferation and IL-2 secretion to varying degrees [69]. Though the nature of the inhibitor components in FVIII is unknown, the immunosuppressive effects of certain FVIII products, particularly when administered in high doses, should be considered [69]. Furthermore, data suggests that VWF complex formation reduces the ability of APCs to process FVIII [70].…”
Section: The Controversial Role Of Vwfmentioning
confidence: 97%
“…Some have suggested that impurities contained in pdFVIII concentrates (e.g., soluble HLA class I, soluble Fas-ligand, and transforming growth factor beta 1) but not rFVIII concentrates may be responsible for the immunomodulating activity, not simply the presence of VWF [68]. FVIII products have been shown to inhibit lymphocyte proliferation and IL-2 secretion to varying degrees [69]. Though the nature of the inhibitor components in FVIII is unknown, the immunosuppressive effects of certain FVIII products, particularly when administered in high doses, should be considered [69].…”
Section: The Controversial Role Of Vwfmentioning
confidence: 98%